SOURCE RETRIEVAL AND TEXT ALIGNMENT CORPUSCONSTRUCTION FOR PLAGIARISM DETECTION (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2022)
For the task of source retrieval, we focus on the process of Download Filtering. For the procedurefrom lumping to seek control, we go for high review, and for the procedure of download separating,we dedicate to enhance accuracy. A vote- based methodology and an order based methodology arefused to channel the seeking results to get the written falsification sources. For the undertaking ofcontent arrangement corpus development, we depict the strategies we use to build the Chinesewritten plagiarism cases. At last, we report the statistics of text alignment dataset submissions.